The Effect Of Trust, Perceived Risk, And Lifestyle On Online Purchase Decisions In E-Commerce - diskhamarzaweny; Rina Andriani; Yeni Sapridawati; Yul Emri Yulis (Cita konsultindo, 2023)
This causal research aims to determine and explain the effect of Trust, Perceived Risk, and Lifestyle on Online Purchase Decisions in E-Commerce among college students. The research using a sample size of 100 active college students as respondents, with purposive sampling method. Sample criteria is active college students in Kuantan Singingi Regency and having made online purchases on E-Commerce at least three times. Data collected with questionnaires and analyzed used Multiple Linear Regression with SPSS Statistics Version 26 software to test hypothesis in this study. The results revealed that Trust and Lifestyle have a positive and significant effect, while Perceived Risk has a negative and significant effect on Online Purchasing Decisions among college students of Kuantan Singingi Regency. Based on the coefficient of determination, Trust, Perceived Risk, and Lifestyle had 75.1% effect on Online Purchasing Decisions, while the remaining 24.9% were influenced by other variables outside of regression that were not examined in this research. Keywords: Trust, Perceived Risk, Lifestyle, Online Purchase Decisions